Pengaruh Subsitusi Tepung Buah Mangrove Rhizophora mucronata DAN Tepung Tapioka Terhadap Kadar Tanin Dan Mutu Organoleptik Kerupuk - Andi Eni Firdani; Asriani Hasanuddin; Roni Hermawan (Faculty of Science and Technology University Ibrahimy, 2022)
This study aims to determine the effect of substitution of R. mucronata mangrove fruit flour and tapioca flour on tannin content and organoleptic quality of crackers. This research was conducted using a completely randomized design (CRD) for testing tannin levels, while for organoleptic testing using a randomized block design (RAK), namely the formulation of mangrove flour and tapioca flour consisting of 5 treatments with a ratio of P1 (10: 90%), P2 (20: 80%), P3 (30: 70%), P4 (40: 60%) and P5 (50: 50%). Each treatment was repeated 3 times so that the total number of treatments was obtained 15. The parameters observed were tannins and organoleptic (sensory) tests including color, aroma, texture, and taste using 30 untrained panelists. Tannin levels were tested using the UV-Vis Spectrophotometer method, tanning standards. The results of this study indicate that the use of substitution of mangrove fruit flour R. mucronata and tapioca flour showed a very significant effect on the texture, taste, color and aroma of crackers in each treatment (0.01%) and had a tannin content value in the range of 6.75. -22.71 mg / 100g. In this study, it can be concluded that the substitution of mangrove fruit flour R. mucronata and tapioca flour produced crackers with the best organoleptic quality found in P2 treatment (20: 80% ratio) with a tannin content of 8.05 mg / 100g.